(untitled) (American Journal of Islam and Society, 2001)
This article reviews Hellenic’ and Islamic ethics before the middle of the eleventh century. It begins with the ethics of the pre-Islamic Arabs and then describes the ethics of the Qur’an, hadith (Prophetic Tradition), adab2, Sufism, theology and philosophy. We attempt to provide here, as far as possible, a comprehensive, but not necessarily exhaustive, overview of the unfoiding of Islamic ethics from the period of Prophet Muhammad to Miskawayh (422/1030), the first Muslim moral philosopher who made a conscious effort to Islamize and integrate Hellenic elements within his ethical treatise and to make it part of the Islamic intellectual legacy. Such an overview is intended to provide an approximate picture of the evolution of Islamic ethical trends, which have modified the old Arabian ideal of muru’ah (manliness) into a new ideal of virtuous happiness in this world and in the Hereafter. Hellenic ethics have inspired Muslim philosophers from the time of Miskawayh to develop a more systematic exposition of Islamic ethics, and we hope that this review of the early ethics of Islam will provide a better appreciation of the early sources that have haped the ethics of later Islamic moralists such as al-Raghib al-Isfahani (d. 433/1050) and al-Ghazzaii (505/1111), who have had a lasting impact on Muslim thinkers up to today.